Podręcznik do nauki języka angielskiego Franciszka Kuszla w świetle jego biografii = Franciszek Kuszel`s textbook for the teaching of English in the light of his biography - Podhajecka, Mirosława (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
In the literature on foreign language teaching Franciszek Kuszel appears sporadically as the author of a Polish-English phrasebook entitled "Rozmowy podręczne dla podróżujących do Londynu Polaków nieumiejących zupełnie Języka Angielskiego" (1857). There are also other extant materials: "Książka Podręczna do Uczenia się Języka Angielskiego dla Uczniów Szkoły Główney w Warszawie" [1864], written for English instruction at the Szkoła Główna Warszawska and reproduced by means of the lithographic method, and "Dziennik czynności osobistych od dnia 25 września 1834", a manuscript source of biographical information. This article has two main purposes: to sketch the biography of the author and take his textbook under a scrutiny.
Keywords: Kuszel, Franciszek; język angielski - nauczanie; dydaktyka; podręcznik; dziennik; English language; teaching; textbook; diary